2008
DOI: 10.1091/mbc.e07-12-1237
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cross-Talk between Three Cardiovascular Regulators: Thrombin Cleavage Fragment of Jagged1 Induces Fibroblast Growth Factor 1 Expression and Release

Abstract: Angiogenesis is controlled by several regulatory mechanisms, including the Notch and fibroblast growth factor (FGF) signaling pathways. FGF1, a prototype member of FGF family, lacks a signal peptide and is released through an endoplasmic reticulum-Golgi-independent mechanism. A soluble extracellular domain of the Notch ligand Jagged1 (sJ1) inhibits Notch signaling and induces FGF1 release. Thrombin, a key protease of the blood coagulation cascade and a potent inducer of angiogenesis, stimulates rapid FGF1 rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
(100 reference statements)
0
18
1
Order By: Relevance
“…Although FGF1 is not a classical target of Notch transcription, ours is not the first evidence of a regulatory relationship between Notch and FGF signaling. In several previous studies, the constitutive activation of canonical (CBF1 dependent) Notch-mediated transcription was found to suppress FGF1 expression, while inhibition of CBF1 and its coactivator MAML induced FGF1 expression and transport into the extracellular compartment (31)(32)(33). Surprisingly, we observed evidence of the opposite, as in vitro Notch activation increased FGF1 transcript levels and produced an FGF1-dependent invasive phenotype.…”
Section: Discussioncontrasting
confidence: 57%
“…Although FGF1 is not a classical target of Notch transcription, ours is not the first evidence of a regulatory relationship between Notch and FGF signaling. In several previous studies, the constitutive activation of canonical (CBF1 dependent) Notch-mediated transcription was found to suppress FGF1 expression, while inhibition of CBF1 and its coactivator MAML induced FGF1 expression and transport into the extracellular compartment (31)(32)(33). Surprisingly, we observed evidence of the opposite, as in vitro Notch activation increased FGF1 transcript levels and produced an FGF1-dependent invasive phenotype.…”
Section: Discussioncontrasting
confidence: 57%
“…Recombinant FGF1:HA adenovirus was produced, purified, and titered as described (Duarte et al, 2008). Briefly, CRE8 cells were transfected with SfiI -digested pAdlox-derived constructs, and infected with the ψ5 virus.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence has demonstrated that fibrinogen alone can augment the proliferation rates of specific carcinoma cells and endothelial cells in response to FGF‐2, and that this appears to be attributable to fibrinogen‐FGF‐2 binding 37, 38. Similarly, thrombin promotes endogenous FGF‐1 expression in endothelial cells39 and FGF‐2 in SMCs,40 upregulates VEGF expression in SMCs via endogenous PDGF and FGF‐2 activity,41 can itself be a significant SMC mitogen and chemoattractant in vitro at concentrations of 0.5 U/mL in a process likely involving FGF‐2 release and FGFR‐1 transactivation,42 and can significantly impact fibrin gel structural and mechanical properties which could affect cellular behavior 43. While thrombin can affect SMC proliferation rates in 2D culture systems, the role of thrombin in modulating SMC proliferation in 3D culture systems is less established.…”
Section: Discussionmentioning
confidence: 99%